Penelitian Persepsi Masyarakat Terhadap Penerapan Biaya Kemacetan (Stu Di Kasus : Kawasan 3 In 1) - Herawati, Herawati (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2010)
T7re main problem of transportation sector in urban aren is congestion. T7rerefore, government isalways looki.ng for solution for that problem. One of tire solution have been impelmented in OKIJakarta is 3 in 1 area whi.ch is implemented on particular congestion links in OKI Jakarta as an effortrestri.ctions on private vehicles usage. Although the si;stem has not successed to reduce tire level ofcongestion. So that, tire goverment tried to impl.ement congestion charging as additional cost topubli.c vehicle user and finally tluzt azn reduce primte z:elzicle users. T7ie goal of this study is to identifiJpeople perception related to congestion cluzrging.T7re method used in this research is a state perference which used discrete choice model. DiscreteOwice Model is a probabilistic model where tire value of each option relates to the respondents withotlier options for a set of alternatives offered. T7ie general form of this model is tire model with tlie logi.cfunction.T7re result of tl1is analysis is if tlie program is renlized nm.1 agree to use primte azrs, agree to usemotora;cle, disagree to shift to publi.c azrs. Snuzrtazrd and sensor si;stem choosen as pm;ment si;stemand cash pm;ment is not choosen bi; private car users. Public is ven; agree if indicatior of pm;mentvalue is time based and disagree if indicator of pm;ment based on distance or time-distance.